Application of machine learning in attentiveness detection from EEG signal - Ridi, Sadia Sobhana; Tandra, Jannatul Farzana; Emon, Mahmudul Hasan; Mahmud, Md Ridwan; Tabassum, Sumaiya (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.